Comparison of Perioperative Radiation Therapy and Surgery Versus Surgery Alone in 204 Patients With Primary Retroperitoneal Sarcoma: A Retrospective 2-Institution Study. Issue 1 (July 2015) - Kelly, Kaitlyn J.; Yoon, Sam S.; Kuk, Deborah; Qin, Li-Xuan; Dukleska, Katerina; Chang, Kevin K.; Chen, Yen-Lin; Delaney, Thomas F.; Brennan, Murray F.; Singer, Samuel
Abstract : Objective: To compare outcomes of patients with retroperitoneal or pelvic sarcoma treated with perioperative radiation therapy (RT) versus those treated without perioperative RT. Background: RT for retroperitoneal or pelvic sarcoma is controversial, and few studies have compared outcomes with and without RT. Methods: Prospectively maintained databases were reviewed to retrospectively compare patients with primary retroperitoneal or pelvic sarcoma treated during 2003–2011. Multivariate Cox regression models were used to assess associations with the primary endpoints: local recurrence-free survival (LRFS) and disease-specific survival. Results: At 1 institution, 172 patients were treated with surgery alone, whereas at another institution 32 patients were treated with surgery and perioperative proton beam RT or intensity-modulated RT with or without intraoperative RT. The groups were similar in age, tumor size, grade, and margin status (all P > 0.08). The RT group had a higher percentage of pelvic tumors ( P = 0.03) and a different distribution of histologies ( P = 0.04). Perioperative morbidity was higher in the RT group (44% vs 16% of patients; P = 0.004). After a median follow-up of 39 months, 5-year LRFS was 91% (95% confidence interval, 79%–100%) in the RT group and 65% (57%–74%) in the surgery-only group ( P = 0.02). On multivariate analysis, RT was associated with better LRFS (hazard ratio, 0.26; P = 0.03). Five-year disease-specific survival was 93% (95% confidence interval, 82%–100%) in the RT group and 85% (78%–92%) in the surgery-only group ( P = 0.3). Conclusions: The addition of advanced-modality RT to surgery for primary retroperitoneal or pelvic sarcoma was associated with improved LRFS, although this did not translate into significantly better disease-specific survival. This treatment strategy warrants further investigation in a randomized trial. Abstract : This study examines advanced-modality radiation therapy for retroperitoneal or pelvic soft-tissue sarcoma. We retrospectively compared 172 patients treated by surgery alone with 32 patients treated by surgery plus radiation therapy. In multivariate analysis, radiation therapy was associated with improved local recurrence-free survival but not disease-specific survival.